2006
DOI: 10.1111/j.1365-2184.2006.00408.x
|View full text |Cite
|
Sign up to set email alerts
|

Protein encoded by HSV‐1 stimulation‐related gene 1 (HSRG1) interacts with and inhibits SV40 large T antigen

Abstract: Herpes simplex virus (HSV)-1 stimulation-related gene 1 (HSRG1) protein expression is induced in HSV-1 infected cells. We found that HSRG1 interacts with SV40 large T antigen (LT) in yeast two-hybrid assay and bimolecular fluorescence complementation (BiFC) assay. This interaction alters LT's regulation of the SV40 promoter and its ability to influence the cell cycle. Choramphenicol acetyl-transferase (CAT) assays revealed that initiation of gene transcription by LT is changed by HSRG1 expression. HSRG1 inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 39 publications
0
5
0
3
Order By: Relevance
“…As a member of the SAND family, it is important to understand the functions of HSRG1. We previously found that HSRG1 specifically interacts with amino acids 132-450 of the SV40 large T antigen, and that transcriptional activity of SV40 promoters activated by large T was inhibited by HSRG1 [10]. We suggested that HSRG1 might have a role in cellular transcriptional regulation.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…As a member of the SAND family, it is important to understand the functions of HSRG1. We previously found that HSRG1 specifically interacts with amino acids 132-450 of the SV40 large T antigen, and that transcriptional activity of SV40 promoters activated by large T was inhibited by HSRG1 [10]. We suggested that HSRG1 might have a role in cellular transcriptional regulation.…”
Section: Discussionmentioning
confidence: 90%
“…Proteins induced by viral infection have been intensively studied [6,7,10] and the functions of these proteins have been gradually clarified. HSRG1, belonging to the conserved SAND protein family, is one of the proteins upregulated in early stages of HSV-1 infection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…T抗原产生相互作用, 并影响大T抗原对SV40 启动子 的转录起始功能 [10] , 该结果提示 HSRG1 具有与转 录调控蛋白相互作用的特性. 因此, 进一步利用酵母 双杂交技术研究了该蛋白分子在细胞内可能的作用 蛋白.…”
Section: 析发现 它能与猴病毒Sv40 的重要转录调控蛋白大unclassified